The re-creation of the Manoelês idiolect - Vieira, Tania Regina; Aguiar, Ofir Bergemann de (Revista de Letras, 2009)
This paper aims at investigating two of Manoel de Barros´s poems extracted from O livro das ignorãças, the poet´s work which has most attracted translations. The analyses will take into account the text in Portuguese as well as its translations, since we believe, as René Etiemble and Ezra Pound do, that studying or making translation is the best way of learning about the work of an author. First of all, the poem VII of Didática de uma invenção, translated to Spanish by Jorge Larrosa and to French by Celso Libânio, will be presented. It is a metapoetic fragment in which the search for the adamic word can be perceived. Next, the poem I of Mundo Pequeno, translated to French by Celso Libânio and to English by João Rache, will be dealt with. In this part, the Pantanal emerges as the generator theme of the barrosian poetics which is characterized by linguistic innovations. The translation modalities of Francis Aubert will support this study, as well as the refl ections of André Lefevere about the rhetoric effects created by the resources used by authors and translators.